Exploring linkages between agriculture and HIV/AIDS: A multilevel study of the impact of agricultural consumption regimes on women’s vulnerability to HIV/AIDS in Kenya - Mwangi, Esther (International Food Policy Research Institute, 2009)
The recognition that the HIV/AIDS epidemic is a major threat to sub Saharan Africa’s economic development has prompted researchers to focus on the economic impacts of the disease. In particular, given the importance of agriculture for livelihoods in sub Saharan Africa (SSA), researchers have investigated the impact of HIV/AIDS on agriculture. Relatively little research has focused on the role agriculture plays in fueling the spread of HIV/AIDS. This study addresses this gap in the literature and examines how agricultural contexts in Kenya influence women’s vulnerability to HIV/AIDS. The study defines vulnerability in terms of upstream factors, that is whether and through what pathways poverty puts people at greater risk of being exposed to the virus.